2022
DOI: 10.1037/dec0000172
|View full text |Cite
|
Sign up to set email alerts
|

Decisions from valuations of unknown payoff distributions.

Abstract: Four experiments are presented that clarify the impact of experience on the way people use valuations. In each of the 100 trials of Study 1, participants were asked to choose between the status quo and an unknown binary lottery based on valuations by two expert systems: a well-calibrated “expert” reporting the expected values, and an expert that ignores the low probability outcome and reports the medians (that equaled the modes). The results suggest that experience decreased the inclination to follow the recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Bolton and Katok (2018) study the efficacy of probability forecasts versus recommendation forecasts. They found that forecasts in the form of a recommendation are prone to a “cry wolf effect”—a tendency to ignore the forecast when the forecast has been wrong in the past (also found in previous studies; e.g., Bliss et al., 1995; Erev et al., 2020; Meyer & Bitan, 2002). Overall, probability forecasts performed better.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Bolton and Katok (2018) study the efficacy of probability forecasts versus recommendation forecasts. They found that forecasts in the form of a recommendation are prone to a “cry wolf effect”—a tendency to ignore the forecast when the forecast has been wrong in the past (also found in previous studies; e.g., Bliss et al., 1995; Erev et al., 2020; Meyer & Bitan, 2002). Overall, probability forecasts performed better.…”
Section: Introductionsupporting
confidence: 58%
“…One obvious alternative, natural language descriptions of uncertainty, has been shown to be ambiguous: Interpretation of verbal descriptions of uncertainty are sensitive to context (e.g., Harris & Corner, 2011; Weber & Hilton, 1990) and vary widely by individual (e.g., Karelitz & Budescu, 2004; Wallsten et al., 1986), limiting their ability to deliver a clear message about risk. Recommendations based on expert assessments of the forecast offer a way around both user numeracy and verbal description shortcomings (Erev et al., 2020). Non‐numeric in nature, recommendations can, in theory, convey the optimal action to the decision maker as effectively as quantitative measures.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows that in 6 of the 16 problems, the difference between the risk‐rates in the two description conditions was significant. In all six cases, the direction of the significant difference can be explained with the assertion that the description of the cues as experts' recommendations increased the tendency to follow the rule “take the risk if the cue includes at least two T's.” In Condition Experts, this rule implies following the modal recommendation and taking the risk when most experts recommend it (see a similar pattern in Erev et al, 2022). Importantly, in five of the six significant cases, following the modal recommendation impaired expected return.…”
Section: Resultsmentioning
confidence: 86%
“…Table 2 shows that in 6 of the 16 problems, the difference between the risk-rates in the two description conditions was significant. In all six cases, the direction of the significant difference can be explained with the assertion that the description of the cues as experts' recom- most experts recommend it (see a similar pattern in Erev et al, 2022).…”
Section: Additional Effects Of the Description Conditionmentioning
confidence: 89%
“…While this set of situations has clear boundaries, it contains many important members. Examples include settings in which safety devices increase accidents (Cohen & Erev, 2018), taxation backfires (YCNE), people over and under-commit to a course of action (Cohen & Erev, 2021), experience reduces the tendency to trust well-calibrated experts (Erev et al, 2022) and it is necessary to enforce rules (Plonsky et al, 2021). Yet, more insight into how people respond to different dimensions of similarity, and how these similarities interact, is necessary to predict behavior when dynamic regularities are easily detectable.…”
Section: Discussionmentioning
confidence: 99%